The Victim and the Means of Protection at his Reach - Cáceres Vázquez, Minerva (Universidad Autónoma de Tamaulipas, 2021)
It is analyzed that it is the victim, as its role in the criminal process was recognized, and the particular case of Mexico is studied in terms of the recognition of a series of fundamental rights obtained from the constitutional reforms to the justice system and in the matter of Human Rights as well as the protection mechanisms that now count. This work focuses on the study of the victim, where an analysis is made of how the State has conceived it throughout history until it reaches the situation it has in the current legislation. Until today thanks to the constitutional reform on the criminal justice and security system published on June 18, 2008, and the diverse one on human rights of June 10, 2011, which outline the fundamental rights they correspond to the victim of the crime and to the victims of human rights violations, prerogatives that are clearly expressed in the General Law of Victims, and begin to be effective in the new accusatory and oral criminal process.